How Do Bank Lending Rates and the Supply of Loans React to Shifts in Loan Demand in the U.K.? - Johann Burgstaller; Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2009)
This paper examines the pass-through from the market interest to the rate charged on bank loans using aggregate data for the U.K. Thereby, we explicitly disentangle credit supply and demand and allow the interest rate charged on loans to depend on the volume of loans. We find that, although banks adjust the lending rate to some extent, they largely accommodate shifts in demand. Overall, our results are consistent with the idea that banks provide insurance against liquidity shocks.
Keywords: E43; G21; 330; Interest Rate Pass-Through; Relationship Banking; Kredit; Nachfrage; Angebot; Zins; Kreditgeschäft; Großbritannien